Frontier contact between chosŏn Korea and Tokugawa Japan - Lewis, James Bryant (RoutledgeCurzon, 2003)
East Asia from 1400 to 1850 was a vibrant web of connections, and the southern coast of the Korean peninsula participated in a maritime world that stretched to Southeast Asia and beyond. Within this world were Japanese pirates, traders, and fishermen. They brought things to the Korean peninsula and they took things away. The economic and demographic structures of Kyongsang Province had deep and wide connections with these Japanese traders. Social and political clashes revolving around the Japan House in Pusan reveal Korean mentalities towards the Japanese connection. This study seeks to d.